Effects of DBDS and DBPC antioxidants on the corrosion of copper strips immersed in transformer oil - Sutan Chairul, Imran; Ab Ghani, Sharin; Shahril Ahmad Khiar, Mohd; Abu Bakar, Norazhar; Syahrani Johal, Muhammad; Nazri Mohamad Din, Mohamad (Institute of Advanced Engineering and Science, 2024)
This paper presents the experimental findings on the effects of antioxidants on the corrosion of copper strips immersed in mineral oil (MO)–antioxidant samples. First, the uninhibited MO was mixed thoroughly with dibenzyl disulphide (DBDS) or 2,6-di-tert-butyl-p-cresol (DBPC) at different concentrations (5, 15, 25, 50, and 200 mg/kg) using a hot plate magnetic stirrer set at a temperature of 73 °C and stirring speed of 750 rpm for 15 min. Following this, the MO–antioxidant samples were poured into separate test vessels and copper strips were added into the vessels. Next, each MO–antioxidant sample was blanketed with nitrogen gas, sealed, and placed in a forced convection laboratory oven. The MO–antioxidant samples were then thermally aged at 150 °C for 48 h. The results showed that the acidity of the MO–antioxidant sample decreased with an increase in the antioxidant concentration, regardless whether the antioxidant was DBDS or DBPC. However, the corrosion of the copper strip worsened with an increase in the antioxidant concentration, where DBDS had a higher relative degree of corrositivity to copper compared with DBPC. In addition, the results showed that a DBPC concentration of 25 mg/kg reduced the the acidity of the MO–antioxidant sample and resulted in a moderate tarnish of the copper strip.